2018
DOI: 10.11648/j.bio.20180604.11
|View full text |Cite
|
Sign up to set email alerts
|

Stem Borer (<i>Eldana saccharina</i> W) Infestation Outbreak in Sugarcane Plantations of Northern Ivory Coast: Management Strategies Under Implementation

Abstract: Heavy stalk borer infestations broke out over the last three cropping seasons in sugarcane plantations of both Ferké sugar mills of Northern Ivory Coast. The study objective was to determine the cause of heavy infestation observed on cane and sugar yields in order to implement a proper pest management strategy. The study which covers from 2006-06 to 2017-18 cropping seasons was based on sampling of all sugarcane plantations at harvest for cane juice analyses and assessment of stalk borer damages in terms of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In Brazil, larvae in 25.77% and 19.01% of internodes resulted in projected losses of 8.80% and 19.80% in sugar production per 1% of bored internodes ( Rossato et al., 2013 ). A study in France found that highly susceptible varieties SP71-8210 and R579 experienced decreased sugar yield and production loss due to sugarcane stem borer damage ( Bi Pene et al., 2018 ). Pakistan, among the top five sugarcane-producing countries, faces numerous borer species that can cause significant yield loss.…”
Section: Biotic Stresses Affect Sugarcanementioning
confidence: 99%
“…In Brazil, larvae in 25.77% and 19.01% of internodes resulted in projected losses of 8.80% and 19.80% in sugar production per 1% of bored internodes ( Rossato et al., 2013 ). A study in France found that highly susceptible varieties SP71-8210 and R579 experienced decreased sugar yield and production loss due to sugarcane stem borer damage ( Bi Pene et al., 2018 ). Pakistan, among the top five sugarcane-producing countries, faces numerous borer species that can cause significant yield loss.…”
Section: Biotic Stresses Affect Sugarcanementioning
confidence: 99%